UMPSA researcher Ts. Dr. Ahmad Taufik develops DeciXion, a smart solution to help organisations make strategic decisions systematically - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 8 August 2025 – Observing the difficulties faced by many organisations in making strategic decisions, a research led by a lecturer from the Faculty of Industrial Management (FPI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Ts. Dr. Ahmad Taufik Nursal has produced DeciXion, a web-based Decision Support System (DSS) developed using the Fuzzy TOPSIS analysis method.